ROK and Arteriolar Myogenic Tone Generation: Molecular Evidence in Health and Disease - El-Yazbi, Ahmed F.; Abd-Elrahman, Khaled S. (Frontiers in Pharmacology, 2017)
The myogenic response is an inherent property of resistance arteries that warrants a relatively constant blood flow in response to changes in perfusion pressure and protect delicate organs from vascular insufficiencies and excessive blood flow. This fundamental phenomenon has been extensively studied aiming to elucidate the underlying mechanisms triggering smooth muscle contraction in response to intraluminal pressure elevation, particularly, Rho-associated kinase (ROK)-mediated Ca2+-independent mechanisms. The size of the resistance arteries limits the capacity to examine changes in protein phosphorylation/expression levels associated with ROK signaling. A highly sensitive biochemical detection approach was beneficial in examining the role of ROK in different force generation mechanisms along the course of myogenic constriction. In this mini review, we summarize recent results showing direct evidence for the contribution of ROK in development of myogenic response at the level of mechanotransduction, myosin light chain phosphatase (MLCP) inhibition and dynamic actin cytoskeleton reorganization. We will also present evidence that alterations in ROK signaling could underlie the progressive loss in myogenic response in a rat model of type 2 diabetes.